Impact of longer working hours on fathers’ parenting behavior when their infants are 6 months old: The Japan Environment and Children’s Study - Kasamatsu, Haruka; Tsuchida, Akiko; Matsumura, Kenta; Hamazaki, Kei; Inoue, Mariko; Inadera, Hidekuni; , the Japan Environment; Children’s Study Group (Frontiers in Public Health, 2023)
Objective Long working hours have been suggested to affect fathers’ parenting behavior, but previously reported findings have been inconsistent. This study examined the association between the working hours and parenting behavior of fathers while accounting for other factors related to their parenting behavior, using data from the Japan Environment and Children Study (JECS), a large cohort study in Japan. Methods Data from 43,159 father-mother pairs were analyzed. The mother assessed the father’s frequency of seven parenting behaviors at 6 months after delivery. Then, each behavior was classified into a high-engagement group (always and sometimes) or a low-engagement group (rarely and never). The father’s weekly working hours was obtained from his responses during partner's pregnancy and was classified into six levels. Results Logistic regression analysis showed that after adjustment for covariates, fathers’ weekly working hours was still inversely associated with the frequency of all parenting behaviors examined in this study (p for trend < .0001). Compared with fathers working ≥ 0 to ≤ 40 h per week, those working > 65 h per week showed the following adjusted odds ratios (95% confidence intervals) for low engagement in parenting behaviors: playing at home, 2.36 (2.07-2.70); changing diapers, 2.03 (1.88-2.19); and bathing the child, 2.00 (1.84-2.18). Conclusion This study suggests that the greater time constraints imposed by longer working hours are a major factor that discourages fathers from engaging in childrearing behavior. Intervention targeting long working hours could contribute to measures aimed at promoting high-engagement parenting behaviors among fathers.